The Influence of Perceptions of Convenience and Perception of Benefits on Interest in Use of Gopay E-Wallet in Surabaya - Tegar Tri Aji Wibowo; Rizky Dermawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study was aims to explain This study is intended to explain the effects of perception of ease and the perception of benefits to the interest of use. The population used in this study was used by e-wallet in surabaya. The method of collecting samples used is non probability sampling with tecmic purposive sampling the number of respondents as many as 72. All tests on smartpls applications indicate that the entire test scores above the required value for it to be declared reli. Studies have shown that perception of ease and perception of benefits has a positive effect on interest in use